Development of Android-Based E-Learning Platform with RBL - STEM Approach to Improve Digital Literacy - Rina Sugiarti Dwi Gita; Fauzan Adhim; H.B.A Jayawardana; Febri Hariyanto (Postgraduate, University of Mataram, 2024)
The utilization of technology is very important in learning in today's digital era. A research-based learning approach that focuses on STEM disciplines is perfect for maximizing the use of technology. The purpose of this study was to determine the feasibility of android-based E-learning Platform with RBL-STEM approach in terms of content validity and construct validity, and android-based e-learning platform with RBL-STEM approach in terms of improving digital literacy skills of TEP graduate students. Development of Android-based E-Learning Platform with RBL - STEM Approach to Improve Digital Literacy of TEP Graduate Students Universitas PGRI Argopuro Jember using Research and Development (R&D) method with ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The results of data analysis and discussion can be concluded that the Android-Based E-Learning Platform with the RBL - STEM Approach developed is declared to meet the eligibility requirements in terms of content validity and construct validity with a mode value (Mo) ≥ 4, and the Android-Based E-Learning Platform with the RBL - STEM Approach developed is declared effective in improving the Digital Literacy skills of TEP Postgraduate Students of Universitas PGRI Argopuro Jember with an N-Gain percentage of 15% in the medium category (0.30-0.70) and 85% in the high category (0.7-1). Thus, Android-Based E-Learning Platform with RBL - STEM Approach can be used to improve the Digital Literacy ability of TEP Graduate Students of Universitas PGRI Argopuro Jember